NOTES ON POPULATION CHARACTERISTICS AND REPRODUCTIVE BIOLOGY OF THE PORTUNID CRAB CHARYBDIS (CHARYBDIS ) FERIATUS (LINNAEUS) AT COCHIN - Padayatti, Pius S (Indian Journal of Fisheries, 2011)
The size frequency distribution and reproductive biology of Chaiybdis (Chatybdis) forktus (Linnaeus) werestudied from the trawl fishery of Cochin during January-March, 1989. The fishery was mainly supportedby adult crab in the size range 60-154 mm for male and 65-120 mm for female. Overall size frequencydistribution showed a unimodal pattern in both sexes, the bulk of the fishery being contributed by thesize groups 80-109 mm C. W. Males formed about two third of the population. The minimum size ofovigerous female measured 66 mm C. W. Fecundity ranged from 52,350 to 3,09,250, the rate of eggproduction being directly proportional to the size. Active breeding of the spedes was noticed throughoutthe period.